Peramalan Kebijakan Untuk Pencegahan Terorisme: Pendekatan Pemolisian Demokratis di Era Digital - Thamrin, Djuni; Widodo, Slamet (Jurnal Keamanan Nasional, 2024)
This research elaborates on terrorism prevention in Indonesia by applying democratic policing in terms of national security.  The discussion of thesis research conducts an evaluative historical review of preventive policy by looking at global impact, terrorism discourse, and the transformation of terrorist networks since 2000. This research uses a descriptive qualitative approach. The interview method with terrorist prisoners as primary data was further deepened by literature review, and observation as secondary data. The results of this study indicate that the future of terrorism is still growing. Forecasting policies in the next 10 years are needed to respond to these issues by:: (1) in combating terrorism propaganda, a necessary response is to establish partnerships with the private sector, strengthen virtual police, and community empowerment and local intelligence; (2) in preventing terrorist recruitment, a social policing is done, strengthen financial intelligence, and increasing social welfare, and (3) in terms of terrorism act, a response is necessary to prevents social division, regional conflict resolution, and strengthen humanization program.